2014
DOI: 10.1021/mp500303a
|View full text |Cite
|
Sign up to set email alerts
|

Computational Predictions of Glass-Forming Ability and Crystallization Tendency of Drug Molecules

Abstract: Amorphization is an attractive formulation technique for drugs suffering from poor aqueous solubility as a result of their high lattice energy. Computational models that can predict the material properties associated with amorphization, such as glass-forming ability (GFA) and crystallization behavior in the dry state, would be a time-saving, cost-effective, and material-sparing approach compared to traditional experimental procedures. This article presents predictive models of these properties developed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(98 citation statements)
references
References 26 publications
2
96
0
Order By: Relevance
“…SMX is 4-amino-N-(5-methylisoxazol-3-yl)-benzenesulfonamide ( Figure 1c) which is used as an antibiotic to inhibit bacterial para-aminobenzoic acid participation in folic acid synthesis that contributes to DNA synthesis 37 . Each of the sulfonamide drugs is limited in solubility and, therefore, in dissolution rate 38,39 . These two drugs, although similar in their melting point, exhibit two characteristics that are relevant to the pursuit of solid solutions, where they differ markedly.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SMX is 4-amino-N-(5-methylisoxazol-3-yl)-benzenesulfonamide ( Figure 1c) which is used as an antibiotic to inhibit bacterial para-aminobenzoic acid participation in folic acid synthesis that contributes to DNA synthesis 37 . Each of the sulfonamide drugs is limited in solubility and, therefore, in dissolution rate 38,39 . These two drugs, although similar in their melting point, exhibit two characteristics that are relevant to the pursuit of solid solutions, where they differ markedly.…”
Section: Methodsmentioning
confidence: 99%
“…These two drugs, although similar in their melting point, exhibit two characteristics that are relevant to the pursuit of solid solutions, where they differ markedly. The solubility of SMX in water is 30 times the solubility of NIF, and SMX is considered a non-glass former 38 , whereas NIF is a glass former 39 . Since SMX is a non-glass former, use of a melt and flash cooling or lyophilization or spray drying to generate the amorphous form will fail; SMX will crystallize instead of forming a glass 38 .…”
Section: Methodsmentioning
confidence: 99%
“…Compounds which demonstrate good glass-forming ability (GFA) and have a low crystallization tendency (good physical stability) are potential candidates for formulation as ASD (5559). In 2010, Baird et al .…”
Section: Current Status Of Research On Amorphous Formulationsmentioning
confidence: 99%
“…31 was then generated which correctly predicted the dry amorphous stability of 78% of the glass-forming drugs using only 2 easily calculated or predicted descriptors, T g and M r . 10 Further studies which aim to predict glass-forming ability and stability include the work of Alhalaweh et al 42 This study confirmed the rule of thumb which Mahlin and Bergstr€ om previously proposed that drugs with M r >300 are glass formers (classes II and III); it was also observed that drugs with M r <200 were noneglass formers or class I according to Baird et al 34 It was not possible to distinguish between class II (nonstable glass formers) and class III (stable glass formers) just using M r . However, Alhalaweh et al 42 successfully built a model that predicted the correct class of compounds in classes II and III with 78% and 69% accuracy, respectively.…”
Section: Mathematical and Statistical Modelsmentioning
confidence: 99%